Visible light photoredox catalysis: generation and addition of N-aryltetrahydroisoquinoline-derived alpha-amino radicals to michael acceptors - Kohls, Paul; Jadhav, Deepak; Pandey, Ganesh; Reiser, Oliver (Organic Letters, 2012)
The photoredox-catalyzed coupling of N-aryltetrahydroisoquinoline and Michael acceptors was achieved using Ru(bpy)(3)Cl-2 or [Ir(ppy)(2)-(dtb-bpy)]PF6 in combination with irradiation at 455 nm generated by a blue LED, demonstrating the trapping of visible light generated alpha-amino radicals. While intermolecular reactions lead to products formed by a conjugate addition, in intramolecular variants further dehydrogenation occurs, leading directly to 5,6-dihydroindolo[2,1-a]tetrahydroisoquinolines, which are relevant as potential immunosuppressive agents.